214k views
5 votes
Solve the equation?

Solve the equation?-example-1
User Manidos
by
5.4k points

2 Answers

3 votes

Answer:

A. p = -4, p = 2.

Explanation:

p^2 + 2p - 8 = 0

Using the quadratic formula;

p = [-2 +/- √(2^2 - 4*1*-8)] / 2

= (-2 +/- √36) / 2

= (-2 +/- 6) / 2

= 4/2 , -8/2

= 2, -4.

User Pietrorea
by
5.1k points
7 votes

Answer:

A

Explanation:

Given

p² + 2p - 8 = 0 ← in standard form

with a = 1, b = 2, c = - 8

Using the quadratic formula to solve for p

p = ( - 2 ±
√(2^2-(4(1)(-8))) / 2

= ( - 2 ±
√(4+32) / 2

= ( - 2 ±
√(36) ) / 2

p =
(-2-6)/(2) =
(-8)/(2) = - 4

p =
(-2+6)/(2) =
(4)/(2) = 2

User RishiC
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.